Ablation of Sam68 in adult mice increases thermogenesis and energy expenditure. Issue 8 (12th July 2021) - Qiao, Aijun; Ma, Wenxia; Deng, Jianxin; Zhou, Junlan; Han, Chaoshan; Zhang, Eric; Boriboun, Chan; Xu, Shiyue; Zhang, Chunxiang; Jie, Chunfa; Kim, Jeong‐a; Habegger, Kirk M.; et al.
Abstract: Genetic deletion of Src associated in mitosis of 68kDa (Sam68), a pleiotropic adaptor protein prevents high‐fat diet–induced weight gain and insulin resistance. To clarify the role of Sam68 in energy metabolism in the adult stage, we generated an inducible Sam68 knockout mice. Knockout of Sam68 was induced at the age of 7‐10 weeks, and then we examined the metabolic profiles of the mice. Sam68 knockout mice gained less body weight over time and at 34 or 36 weeks old, had smaller fat mass without changes in food intake and absorption efficiency. Deletion of Sam68 in mice elevated thermogenesis, increased energy expenditure, and attenuated core‐temperature drop during acute cold exposure. Furthermore, we examined younger Sam68 knockout mice at 11 weeks old before their body weights deviate, and confirmed increased energy expenditure and thermogenic gene program. Thus, Sam68 is essential for the control of adipose thermogenesis and energy homeostasis in the adult.